INVESTIGATION OF MAGNETIC GOLD LOSSES IN A GOLD RECOVERY CIRCUIT (Comprehensive Journal of Science, 2025)
A study was conducted to investigate the occurrence of high gold grades in a carbon fine collected from the gold recoverycircuit in a gold Mine. The research revealed that fine magnetic particles present in the overflow from the carbon fines tankcontained significantly elevated gold concentrations, in the range from 2,000 to 7,000 g/t, with the -37 micron fraction reachingvalues as high as 17,000 g/t. Scanning electron microscopy (SEM) analysis showed that gold was adhered to the surfaces ofiron particles. The objective of the investigation was to identify the processes responsible for gold attachment to magnetic ironparticles and to propose process modifications to minimize gold losses within the carbon circuit. Various samples from thegold recovery circuit solids and solutions were collected and analyzed. There are two potential mechanisms proposed: goldcementation onto iron surfaces, and heterocoagulation of colloidal gold with iron oxides within the elution column. Theseparation of gold from the cathode in the electrowinning (EW) cell and the reduction of the gold–cyanide complex to metallicgold in the carbon regeneration kiln were identified as a potential source of colloidal gold. SEM–EDX analysis further indicatedthat the main sources of iron were natural magnetite and roasted iron sulfides. The formation of dendritic gold within the carbonregeneration kiln is believed to occur through thermal reduction of gold.
Keywords: Cyanide; leach; caustic; iron; gold; precipitation; losses; settling; carbon